Oxidative stress-induced apoptosis of osteoblastic MC3T3-E1 cells by hydroxyapatite nanoparticles through lysosomal and mitochondrial pathways. Issue 21 (24th February 2017) - Jin, Yi; Liu, Xiaolong; Liu, Huifang; Chen, Shizhu; Gao, Chunyue; Ge, Kun; Zhang, Cuimiao; Zhang, Jinchao
Abstract : Hydroxyapatite nanoparticles (HAPs) cause apoptosis of osteoblastic MC3T3-E1 cells through oxidative stress-induced lysosomal and mitochondrial pathway. Abstract : Hydroxyapatite nanoparticles (HAPs) are increasingly utilized in biomedical fields including dental composites, bone tissue engineering and orthopedic implants due to its similar properties to bone minerals. With their widespread use, toxicological effects of HAPs have aroused people's close attention. However, the potential toxic effects of HAPs on bone cells are poorly understood. In our present work, the HAPs with aspect ratios of 4 were synthesized by a hydrothermal method and characterized by transmission electron microscopy (TEM), X-ray diffractometry (XRD), dynamic light scattering (DLS) and photoluminescence (PL). The cytotoxicity of HAPs on MC3T3-E1 cells and the relevant mechanisms were further studied. The results proved that HAPs could be uptaken into MC3T3-E1 cells via macropinocytosis-mediated endocytosis pathway, and mainly localized in lysosome. HAPs inhibited the cells proliferation in dose- and time-dependent manners. Results from annexin V-FITC/PI apoptosis assay showed that HAPs induced cell apoptosis significantly, and the mechanism of apoptosis was related to oxidative stress. HAPs induced ROS generation and antioxidant enzymes superoxide dismutase (SOD) and glutathion peroxidase (GSH-Px) decrease, which not only induced a lysosome-dependent damage pathway via lysosomal membrane permeabilization (LMP) and increased the release of cathepsins B, but also a mitochondria-dependent damage pathway via counter regulating expressions of bax and bcl-2, decrease of mitochondrial membrane potential (MMP), activation of caspase3. In addition, the ROS also caused DNA damage. In summary, HAPs induces apoptosis through oxidative stress-induced lysosomal and mitochondrial pathways. Our study will provide some valuable data for biomedical applications of HAPs in the future.